2002
DOI: 10.1159/000049400
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Efficacy of Topical Preparations with 10% Hamamelis Distillate in a UV Erythema Test

Abstract: In 40 volunteers the efficacy of three lotions with 10% hamamelis distillates from different suppliers, two vehicles, dimethindene maleate 0.1% gel, hydrocortisone 1% cream and hydrocortisone 0.25% lotion were investigated in a modified UV erythema test with three UV dosages (1.2, 1.4 and 1.7 MED). The test preparations were applied occlusively over a 48-hour period following irradiation. Chromametric measurement of redness and visual assessment were performed 24, 48 and 72 h after induction of erythema. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
0
23
0
3
Order By: Relevance
“…As positive controls, different corticosteroids have been used, from 0.5% hydrocortisone to potent corticosteroids like 0.1% betamethasone [3-5, 8, 9] . Also the sample size varies from 5 to 40 subjects [1,3,4,10,11] . In recent studies, a trend towards larger sample sizes can be observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As positive controls, different corticosteroids have been used, from 0.5% hydrocortisone to potent corticosteroids like 0.1% betamethasone [3-5, 8, 9] . Also the sample size varies from 5 to 40 subjects [1,3,4,10,11] . In recent studies, a trend towards larger sample sizes can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, a trend towards larger sample sizes can be observed. Finally, different methods have been used to measure the erythema (visual scores, chromametric measurement) [1,4] .…”
Section: Introductionmentioning
confidence: 99%
“…One of the components of the patientʼs ink was H. virginiana, a kind of witch hazel that has been linked to anti-inflammatory properties, especially in cases of photodermatitis [37,38,39,40] and colonic cancer [41,42], due to a molecule called hamamelitannin, with anti-TNF properties (in vitro inhibition of TNF-mediated cell death and DNA fragmentation) [43] and scavenging activity against reactive oxygen species [42,44,45]. Even if it were attractive to assume that H. virginiana could have had an inhibitory effect over the purpuric rash, we would have to presume that functional levels of the active principle still remained in the skin 5 years after its injection, which is to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…По химической структу-ре диметиндена малеат представляет собой рацеми-ческую смесь, в которой один из энантиомеров, R(-) диметинден, обладает более мощным антигистамин-ным действием, способствуя снижению проницае-мости мелких сосудов и капилляров при аллергиче-ских реакциях немедленного типа. Препарат также является мощным стабилизатором мембран тучных клеток, что способствует опосредованному противо-воспалительному эффекту [10,17,29].…”
Section: антигистаминное действиеunclassified